STUDY OF BIOCHEMICAL MARKERS OF OSTEOGENESIS IN CASE OF BONE ALLOGRAFTS INCORPORATION IN RATS WITH FOLLOWED AFTER SURGERY ADMINISTRATION OF CISPLATIN AT THE DIFFERENT METHODS OF IMPLANT STERILIZATION - Vyrva, Oleg; Golovina, Yanina; Leontyeva, Frieda; Malyk, Roman (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Bone allografts are commonly used for surgical treatment of cancer patients. However, such complications as violation of allograft fusion, its lysis and fractures, infection lead to additional research in this field of medicine. Objective. To study changes in biochemical osteogenesis markers under the action of cytostatics on the process of incorporation of bone allografts. Methods. The work was performed on 20 male white rats (age at the beginning of the experiment 5–6 months). All animals have a perforated defect in the distal metaphysis of the femur filled with bone allograft (diameter 2 mm, height 3 mm), γ-radiation sterilized (Control-1 and Experiment-1) or saturation of the antibiotics sterilized (Control-2 and Experiment-2). In groups «Control» 14 days after implantation intraperitoneally injected 2.0–2.4 ml of 0.9 % sodium chloride solution, in the groups «Experiment» — cisplatin at a dose of 2.5 mg/ kg once. 30 days after surgery, blood glycoproteins, total protein, Ca, chondroitin sulfates, acidic and alkaline phosphatase activity were evaluated. The index of mineralization (ratio of alkaline to acid phosphatases), degree is analyzed mineralization (ratio of calcium to protein). Results. In the experimental groups, compared with the control, a significant decrease in total protein and values was determined: total calcium, which indicates the suppression of processes mineralization during remodeling of bone tissue of the recipient and allograft. The highest indicators of activity acid phosphatase were recorded in groups Experiment-1 and Experiment-2, reflecting the predominance of resorption over bone formation. The degree of mineralization in the experimental groups was higher than in the control, and the mineralization index was significantly smaller. Conclusions. The detected changes in the values of biochemical markers of bone metabolism reflect the negative effect of cisplatin on osteogenesis under the conditions of allograft implantation, which leads to the lack of their fusion with the recipient bone.